2014
DOI: 10.18632/oncotarget.1686
|View full text |Cite
|
Sign up to set email alerts
|

RB1 gene inactivation by chromothripsis in human retinoblastoma

Abstract: Retinoblastoma is a rare childhood cancer of the developing retina. Most retinoblastomas initiate with biallelic inactivation of the RB1 gene through diverse mechanisms including point mutations, nucleotide insertions, deletions, loss of heterozygosity and promoter hypermethylation. Recently, a novel mechanism of retinoblastoma initiation was proposed. Gallie and colleagues discovered that a small proportion of retinoblastomas lack RB1 mutations and had MYCN amplification [1]. In this study, we identifed recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
112
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 39 publications
6
112
2
3
Order By: Relevance
“…In one study, high-level MYCN amplifications were found only in those retinoblastomas in which RB mutations were undetected (3). In a more recent study, however, 8 of 94 retinoblastomas had more than 10 MYCN copies, and 6 of 8 of these MYCN-amplified retinoblastomas had at least 1 hit in the RB gene detected (2). Thus, a subset of retinoblastomas shows MYCN amplification, even in the absence of detected RB mutation, while in other retinoblastomas, MYCN amplification and RB mutations co-occur.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In one study, high-level MYCN amplifications were found only in those retinoblastomas in which RB mutations were undetected (3). In a more recent study, however, 8 of 94 retinoblastomas had more than 10 MYCN copies, and 6 of 8 of these MYCN-amplified retinoblastomas had at least 1 hit in the RB gene detected (2). Thus, a subset of retinoblastomas shows MYCN amplification, even in the absence of detected RB mutation, while in other retinoblastomas, MYCN amplification and RB mutations co-occur.…”
Section: Discussionmentioning
confidence: 91%
“…RB deletion and MYCN amplification are the two most frequent focal alterations occurring in human retinoblastoma, and these alterations often co-occur in the same tumor (2). MYCN amplifications in the absence of RB mutations or deletions have been described previously (2,3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 1% of RB (usually unilateral) is due to somatic MYCN amplification rather than loss of RB1 function (4). Another study demonstrated three RBs with focal chromothripsis in the tumor tissue disrupting the RB1 locus, suggesting that somatic acquisition of these complex structural rearrangements can play a role in RB1 tumor-suppressor inactivation (5).…”
Section: Hereditary Rb: Introductionmentioning
confidence: 99%